The Influence of Reward and Punishment on Employee Performance with Discipline as an Intervening Variable at PT. Mekar Sari Mulya - Maghdalena, Zema Indra; Buniarto, Edwin Agus; Muttaqien, Zaenul (Ekonomis: Journal of Economics and Business, 2025)
This study aims to test and analyze the effect of reward and punishment on employee performance with discipline as an intervening variable at PT Mekar Sari Mulya. This type of research is quantitative research. The sample in this study was obtained using probability sampling technique with random sampling approach. The population used was employees of PT Mekar Sari Mulya with a sample of 50 respondents. Data was collected using a questionnaire method. The analysis method used is Partial Least Square (PLS) with the help of SmartPLS software. The results showed that Reward has a significant effect on Employee Performance. Punishment has no effect on employee performance. Discipline has a significant effect on employee performance. Reward has a significant effect on employee performance through discipline. Punishment affects employee performance through discipline.